Japanese Flipped Classroom Knowledge Acquisition Based on Canvas Web-Based Learning Management System - Shi, Wan Li; Zhang, Yu Hui (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Since 2010, flipped classrooms and Canvas-based online learning spaces have been widely recognized by colleges and universities, changing the traditional Chinese learning space.OBJECTIVES: To ensure that students learn effectively, learning management systems must be applied. The issue of integrating classroom space and electronic learning management systems gives students the freedom and flexibility to manage their time after school.METHODS: In this study, Japanese language skills were learned through questionnaires, interviews, and classroom observations, and two students with similar disciplines and conditions were selected from the experimental and control categories for a learning reform experiment during the semester's learning cycle.RESULTS: By comparing the characteristics and effectiveness of the experimental and tutorial courses, an appropriate Japanese language course was designed and developed, and some constructive suggestions were made for the application of the Canvas network to Japanese language courses.CONCLUSION: The use of flipped teaching methods and structured e-learning methods in the education of basic Japanese language majors can improve students' academic performance and sense of cooperation.
Keywords: Canvas; web-based learning management system; Japanese language; flipped classroom